2013
DOI: 10.1088/0957-4484/24/24/245302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight distribution on e-beam exposure properties of polystyrene

Abstract: Polystyrene is a negative electron beam resist whose exposure properties can be tuned simply by using different molecular weights (Mw). Most previous studies have used monodisperse polystyrene with a polydispersity index (PDI) of less than 1.1 in order to avoid any uncertainties. Here we show that despite the fact that polystyrene's sensitivity is inversely proportional to its Mw, no noticeable effect of very broad molecular weight distribution on sensitivity, contrast and achievable resolution is observed. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…The sensitivity is similar to that of low molecular weight polystyrene [21], and may be improved drastically by using higher molecular weight sodium PSS, as for chain cross-linking polymer resist the sensitivity (μC/cm 2 ) is expected to be roughly inversely proportional to its molecular weight (kg mol −1 ) [22]. The polydispersity of our sodium PSS is unknown, but it is not expected to have a significant effect on its exposure property [23]. As for the resist contrast, one way to enhance it is to use lower molecular weight, but at the cost of reduced sensitivity.…”
Section: Methodsmentioning
confidence: 82%
“…The sensitivity is similar to that of low molecular weight polystyrene [21], and may be improved drastically by using higher molecular weight sodium PSS, as for chain cross-linking polymer resist the sensitivity (μC/cm 2 ) is expected to be roughly inversely proportional to its molecular weight (kg mol −1 ) [22]. The polydispersity of our sodium PSS is unknown, but it is not expected to have a significant effect on its exposure property [23]. As for the resist contrast, one way to enhance it is to use lower molecular weight, but at the cost of reduced sensitivity.…”
Section: Methodsmentioning
confidence: 82%
“…It is not possible to derive a meaningful resist contrast from this curve, although clearly the contrast is very low. The low contrast is not a result of the resist's broad molecular weight distribution, as it has been shown that the polydispersity (defined as Mw/Mn, the ratio of weight averaged molecular weight and number averaged molecular weight) had an insignificant effect on polystyrene's exposure properties (Dey and Cui 2013 Fig. 1(b)…”
Section: Resultsmentioning
confidence: 98%
“…PS is a very versatile negative resist offering tunable sensitivity and contrast simply by varying its molecular weight. 15,16 PS has a dry etching rate very close to that of ZEP-520A (positive) resist, and is two to three times slower than PMMA because PMMA is a linear polymer with higher oxygen content and higher radiation yield of chain scission reactions, whereas ZEP-520A has a stable phenyl group in its chemical structure. [17][18][19] PS film of 400 nm thickness was coated on silicon wafer using spin coating method.…”
Section: Methodsmentioning
confidence: 97%